Transcranial direct current stimulation for the treatment of post-stroke depression: A systematic review - Hao, Wenjian; Liu, Yong; Gao, Yuling; Gong, Xiaoyang; Ning, Yi (Frontiers in Neurology, 2023)
Background: Post-stroke depression (PSD) is not only a frequent neuropsychiatric manifestation secondary to stroke but also associated with disability, poor rehabilitation outcomes, sleep disorders, cognitive impairment and increased mortality. Transcranial direct current stimulation (tDCS), a primary modality of non-invasive brain stimulation (NIBS), has shown its promising clinical results in the rehabilitation of PSD patients recently. The primary aim of this systematic review is to assess the effects of tDCS for PSD. Methods: PubMed and Cochrane databases were used for papers identification up to May 2022. Only English language studies and published data were taken into consideration. Methodological quality of selected studies were assessed according to the modified Sackett Scale, based on Physiotherapy Evidence Database (PEDro) scores. Results: Six experimental studies were included for the PSD treatment of tDCS and all of them reported that, following the intervention of tDCS, the experimental group shows a statistically significant decrease in the depression level in accordance with different assessment scales. Conclusions: This article simply aims at providing a comprehensive overview of the raw data reported in this field to date. Based on the current evidence, tDCS presents promising results for the treatment of PSD. Moreover, tDCS is also effective in PSD patients with aphasia or CPSP. However, an optimal stimulation protocol is needed to formulate. Thus, the development of robustly controlled, randomized and high-quality clinical trials to further assess the utility of tDCS as a therapeutic tool for the treatment of PSD survivors is encouraged.